DAMPAK KEBIJAKAN PEMBANGUNAN KEHUTANAN TERHADAP PENDAPATAN MASYARAKAT MISKIN DI KALIMANTAN TIMUR : SUATU PENDEKATAN MODEL SISTEM NERACA SOSIAL EKONOMI - Agus Justianto (School of Business, Bogor Agricultural University (SB-IPB), 2006)
The objective of this study is to evaluatethe impact of selected forest policies on the incomes of the poor in East Kalimantan. A Social Accounting Matrix Approach of1995 and 2003 for Kalimantan Timur wasdeveloped to analyze linkages among socio-economic factors within the region,including poverty, income distribution, and economic development. Nine policyalternatives for the period 1995-2003 were then simulated using the Model toevaluate which would be most suitable for improving the income of the poor wholive in or near forest areas. Based on the comparison of economic performancein Kalimantan Timur before and after the decentralization era (1995 and 2003),the results indicate that the forest sector's contribution to the GDP of Kalimantan Timur decreased after the onset of thedecentralization era. The average disposable income of forest households in1995 and 2003 is the lowest of all household groups. By using poverty mapping,it was found that most of the population living in protection forests are poor,while that living in production forest areas and forest lands intended to beset aside for other purposes is relatively better off. Forestry activitieswhich had the most significant effect in generating income for poor people in Kalimantan Timur were small-scale forest industries ofvarious types. However, in general, forest households did not receive much inthe way of benefits from forestry activities and there is a very low multiplierof forestry sector activities for forest households. Small-scale forestindustries have provided a better income distribution to all groups of foresthouseholds, especially for the poor. Keywords: poverty, economicwelfare, income distribution, social accounting matrix, multiplier, policyimpact